1981
DOI: 10.1136/bmj.282.6270.1103
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and urodynamic studies in 100 elderly incontinent patients.

Abstract: Clinical details were noted and urodynamic studies carried out on 100 elderly patients referred to an incontinence clinic, of whom 48 attended as day patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
4
2

Year Published

1982
1982
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(57 citation statements)
references
References 13 publications
4
47
4
2
Order By: Relevance
“…First of all they are more impaired cognitively, both in relation to their long-term and short-term memory. The disagreement between this finding and that reported elsewhere [7] can be explained by the fact that cognitive impair ment was not the entry criterion in the study by Castleden ct al. [7], hence about half of its subjects reached the maximum mental test score of 10.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…First of all they are more impaired cognitively, both in relation to their long-term and short-term memory. The disagreement between this finding and that reported elsewhere [7] can be explained by the fact that cognitive impair ment was not the entry criterion in the study by Castleden ct al. [7], hence about half of its subjects reached the maximum mental test score of 10.…”
Section: Discussioncontrasting
confidence: 55%
“…Castleden et al [7] have reported no correlation between mental test scores and urodynamic measurements in patients with unstable bladders and concluded that in most elderly patients urinary incontinence is not associated with cerebral disease. These nega tive results, however, might be explained by the relative insensitivity of the cognitive scale utilized and by the type of population sampled by these workers [14], In addition, there is the finding that incontinence may fol low age-related neurogenic damage to the sphincters [13].…”
mentioning
confidence: 99%
“…To assess the aging changes in the urinary bladder in humans, invasive procedures, such as catheterization, cystoscopy or biopsies are required, which may carry a risk for the patient. Moreover, it is difficult to precisely discriminate between dysfunctions belonging to pathology from those related to aging (Castleden et al, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…With continued therapeutic advances, such misdiagnoses will assume increased importance. Our findings may also partially explain the often-reported discrepancy between symptoms and urodynamic diagnosis [Resnick, 19901. In retrospect, studies that evaluated older individuals and disregarded low-pressure involuntary detrusor contractions [Hilton and Stanton, 1981;Castleden et al, 1981;Eastwood and Warrell, 1984;Ouslander et al, 1987Ouslander et al, , 1989Lord and Eastwood, 19941 may have misclassified a substantial proportion of patients with DHIC. Similarly, "abnormal" urethral function in many older women may actually reflect physiologic decreases in sphincter pressure due to low-pressure involuntary contraction of DHIC rather than ' 'urethral instability" or intrinsic sphincter deficiency [McGuire, 19881.…”
Section: Discussionmentioning
confidence: 98%